The great 1950 Assam Earthquake revisited: field evidences of liquefaction and search for paleoseismic events - Reddy, DV; Nagabhushanam, Pasupuleti; Kumar, Devender; Sukhija, Balbir S; Thomas, PJ; Pandey, Anand K; Sahoo, Radhendra Nath; Prasad, GV Ravi; Datta, Koushik (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1306 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.